The rise of new Dalit women in Indian historiography - Paik, Shailaja (History compass, 2018)
Especially since the political turmoil of the 1990s, scholars have focused on the marginalized histories of Dalit ("Untouchable") communities in India. Yet these investigations also concentrated exclusively on the male Dalit community. Only recently, however, scholars have focused their attention on Dalit women as "subjects" of study. Dalits are dominated and dominating at the same time. My article examines Dalit women's lifeworlds under double patriarchy in colonial and post-colonial India to highlight the contributions of scholars in understanding how different Dalit women are negotiating, challenging, politicizing, and transforming conditions of their discriminated Dalit status: as sexed women and caste Dalit. I theorize and focus on ways "new" Dalit women engaged with the incremental intersecting technologies of caste, class, gender, sexuality, and community to carve out their subjectivity, agency, respectability, and honor in modern India. To this end, I dwell on a variety of themes—generative gender and "new" Dalit women, upper-caste prejudice, community, patriarchy, honor, and formal education to illuminate the changing sociality and complexities of Dalit women's worlds. My review article demonstrates that Dalit women's universal perspectives and historical and political practices are deeply democratic and as such have the potential of engaging in inclusive and productive politics, building solidarities, and actually reshaping the larger fields of South Asian Studies, India Studies, Dalit Studies, and Gender Studies.